Measuring Strain of the Lattice Towers - Vladimir Dekys; Jozef Broncek (Communications - Scientific letters of the University of Zilina, 2012)
The paper deals with strain measuring of bolted steel lattice high voltage tower structure on the test field. This measurement was associated to the test according to international standard IEC 60652, Ed. 2.0. If the tower is simulated as a truss structure and we expect the linear behavior of this object then the test data and calculation may show variations. The displacements of screw joint were detected as a source of this variation or non linear properties of structure. The key to this conclusion was detection of peak in measurement data.